2015
DOI: 10.1016/j.neuroimage.2014.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention effects on early integration of social signals: Same timing, modulated neural sources

Abstract: Humans combine co-emitted social signals to predict other's immediate intentions and prepare an adapted response. However, little is known about whether attending to only one of co-emitted social signals impacts on its combination with other signals. Here, using electroencephalography, we address selective attention effects on early combination of social signals. We manipulated three visual cues: gaze direction, emotional expression, and pointing gesture, while participants performed either emotion or gaze dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
5
13
0
Order By: Relevance
“…These findings are consistent with a tremendous of evidence that modulations of early neural responses by biological salient events (e.g., superior hierarchy) are evident in attention-limited environments (Carretié et al, 2004;El Zein et al, 2015;Olofsson et al, 2008). In accord with current findings, previous behavioral studies have demonstrated that high-status targets attract attentional bias in both attended and unattended contexts (Dalmaso et al, 2012;Foulsham et al, 2010).…”
Section: Number Of Stars Taskssupporting
confidence: 92%
“…These findings are consistent with a tremendous of evidence that modulations of early neural responses by biological salient events (e.g., superior hierarchy) are evident in attention-limited environments (Carretié et al, 2004;El Zein et al, 2015;Olofsson et al, 2008). In accord with current findings, previous behavioral studies have demonstrated that high-status targets attract attentional bias in both attended and unattended contexts (Dalmaso et al, 2012;Foulsham et al, 2010).…”
Section: Number Of Stars Taskssupporting
confidence: 92%
“…A growing body of literature concurs with evolutionary accounts by highlighting a functional and anatomical link between neural systems that sustain emotional appraisal and those that underlie action preparation (de Gelder, Snyder, Greve, Gerard, & Hadjikhani, 2004; Grèzes, Valabregue, Gholipour, & Chevallier, 2014; Pichon, de Gelder, & Grezes, 2012; Van den Stock, 2011). Moreover, and in agreement with the present results, the influence of emotion stimuli on motor-related areas was observed from 150ms to 300ms post-stimulus onset (Borgomaneri, Gazzola, & Avenanti, 2014; Conty et al, 2012; El Zein, Gamond, Conty, & Grèzes, 2015a; El Zein et al, 2015b; Hortensius, de Gelder, & Schutter, 2016). We therefore suggest that the early potentiation of premotor activity during emotion decisions is related to the behavioral relevance for the observer of the perceived threat rather than its sensory properties.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is likely that amygdala hyper-vigilance is involved, as previous studies have demonstrated that the amygdala can trigger and inhibit motor responses and/or modulate motor programs in emotionally specific contexts (LeDoux, 2000; Sagaspe et al , 2011). Additionally, El Zein et al (2015) demonstrated that healthy individuals with high anxiety show hyper-vigilance to potentially threatening stimuli by way of earlier electroencephalogram signals in the motor cortex compared to low anxiety individuals. Thus, it is possible that emotion processing in at-risk adolescent females influences both the amygdala and motor-related regions.…”
Section: Discussionmentioning
confidence: 99%